Deconstructing Power Relations and Language Asymmetry in the Documentary Pesta Babi: A Critical Pragmatics Analysis - Ismail Marzuki; Wahid Eko Purwanto; Juwilsi Thianci Rawung (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The documentary film Pesta Babi (2024) documents contemporary colonial practices in South Papua through the National Strategic Project (Proyek Strategis Nasional/PSN) on food and energy, which implicates a network of power encompassing the state apparatus, military, corporations, and religious institutions. This study aims to deconstruct the power relations and language asymmetry operating within the utterance texts of the documentary, employing the framework of Critical Pragmatics. Data were derived from the film's oral transcripts, comprising utterances from state officials, indigenous Papuan communities, corporate representatives, and church leaders. A qualitative method was employed through Critical Pragmatics-based oral discourse analysis. The analysis reveals four dominant patterns: (1) legitimation through institutional euphemisms such as "National Strategic Project" and "national food barn"; (2) delegitimation of indigenous voices through lexical marginalisation; (3) speech act asymmetry in interactions between power agents and indigenous communities; and (4) the indigenous community's counter-discourse as a practice of pragmatic resistance. These findings affirm that language is not merely a medium of communication, but an active instrument that reproduces and sustains structural domination. This study contributes to the development of Critical Pragmatics as an analytical tool for examining the discourse of contemporary colonialism in Indonesia.